Chinese trade & investment in the 21st century: the impact of the Belt and Road Initiative on industrialization in developed & less developed economies - Cahill, Michael J., author; Roberts, Anthony, advisor; Mahoney, Pat, committee member; Harris, Peter, committee member (Colorado State University. Libraries, 2024)
Over the past few decades, China's rise as a global industrial leader has profoundly impacted developed and less developed economies. Most recently, the Chinese government has pursued the Belt and Road Initiative (BRI) to increase its reach and integration into the global economy through trade and investment agreements with roughly 147 countries. Drawing on longitudinal data from 124 countries, I analyze the effects of Chinese trade and investment on the industrialization of developed and less developed economies in the 21st century. Specifically, I analyze whether participation in BRI agreements moderates these effects. The results indicate that Chinese trade and investment increase industrial employment and growth, especially in countries participating in the BRI. However, Chinese trade and investment have a more extensive negative impact on industrial productivity within BRI countries than their non-participating counterparts. While the results are mixed on the benefits and consequences of increased bilateral relations with China, they depict an interesting picture of how Chinese trade and investment affect foreign economies.
Keywords: Chinese investment; industrialization; Chinese trade; Belt and Road Initiative